2016
DOI: 10.3390/ijms17071147
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Associated with Altered Gut Microbiota in Children with Eczema: A Systematic Review

Abstract: Eczema is a common skin condition that impairs children’s daily life activities and quality of life. Previous research shows that gut microbiome composition plays an important role in the development of eczema. The present review summarizes evidence on environmental factors related to altered gut microbiota in children with eczema. We searched Medline, PubMed, Embase, and the Cochrane database of Systematic Reviews through October 2015. The search strategy focused on articles published in peer-reviewed, Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…Chan et al ., in a review of four cohort and two case–control studies (1990 participants), concluded that a number of external factors may contribute to altered gut microbiota in children with AE, including length of gestation, mode of delivery, breast‐feeding, antibiotic use, number of older siblings and other lifestyle factors. However, failure to control for important confounders and heterogeneity in the methods used to assess gut microbiota made it impossible to draw conclusions about how these factors may influence the development of AE.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Chan et al ., in a review of four cohort and two case–control studies (1990 participants), concluded that a number of external factors may contribute to altered gut microbiota in children with AE, including length of gestation, mode of delivery, breast‐feeding, antibiotic use, number of older siblings and other lifestyle factors. However, failure to control for important confounders and heterogeneity in the methods used to assess gut microbiota made it impossible to draw conclusions about how these factors may influence the development of AE.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The prevalence of child eczema is higher in affluent than non‐affluent countries . The prevalence in developed countries for instance Australia, New Zeeland, and United Kingdom is more than 20% whereas in developing countries such as Indonesia, Vietnam, and India is less than 10% .…”
Section: Introductionmentioning
confidence: 98%
“…The gastrointestinal tract is home to microorganisms that live in a symbiotic relationship with the host, and are key determinants of health and disease by influencing nutrient absorption, barrier function, and immune development [24,25]. Recent investigations revealed that changes in gut microbiota and their metabolites have implications in many inflammatory and gastrointestinal diseases, such as asthma, arthritis, functional gastrointestinal disorders, inflammatory bowel disease, and wound-healing [26].…”
Section: Discussionmentioning
confidence: 99%